2005
DOI: 10.1128/jb.187.2.512-521.2005
|View full text |Cite
|
Sign up to set email alerts
|

Probing Direct Interactions between CodY and theoppDPromoter ofLactococcus lactis

Abstract: CodY of Lactococcus lactis MG1363 is a transcriptional regulator that represses the expression of several genes encoding proteins of the proteolytic system. These genes include pepN, pepC, opp-pepO1, and probably prtPM, pepX, and pepDA2, since the expression of the latter three genes relative to nitrogen availability is similar to that of the former. By means of in vitro DNA binding assays and DNase I footprinting techniques, we demonstrate that L. lactis CodY interacts directly with a region upstream of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 58 publications
2
73
0
Order By: Relevance
“…From the genome comparison with L. lactis IL1403, it can be concluded that opp-2 is the original copy of this locus. In L. lactis MG1363, the oppD1 promoter is regulated by CodY (24). A clustalW analysis of the upstream region of oppD1, oppD2, and oppD of L. lactis IL1403 showed marked differences (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…From the genome comparison with L. lactis IL1403, it can be concluded that opp-2 is the original copy of this locus. In L. lactis MG1363, the oppD1 promoter is regulated by CodY (24). A clustalW analysis of the upstream region of oppD1, oppD2, and oppD of L. lactis IL1403 showed marked differences (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments showed that isoleucine is the most important effector among BCAA for CodY repression (this work; den Hengst et al, 2005;Shivers & Sonenshein, 2004). Since the CodY signal in L. lactis is essentially mediated by isoleucine, excess of this amino acid in the environment leads to growth inhibition by blocking inappropriately CodY-dependent biosynthesis pathways.…”
Section: Isoleucine Signal and Nitrogen Metabolismmentioning
confidence: 99%
“…Moreover, the CodY-box is found in the CodY-protected region from the oppD promoter region of L. lactis (two CodY-boxes) and from the ilvB, citB, dpp, fla-che, comK and sfrA promoter regions of B. subtilis (Bergara et al, 2003;den Hengst et al, 2005;Kim et al, 2003;Serror & Sonenshein, 1996a, b;Shivers & Sonenshein, 2004). Moreover, mutations and deletions carried out on the promoter regions of dppA, hut and ureA of B. subtilis and oppD of L. lactis and that affect CodY regulation are within or immediately adjacent to the CodY-box (Eda et al, 2000;Serror & Sonenshein, 1996a;Wray et al, 1997;Wray & Fisher, 1994).…”
Section: Cody Targets In Gram-positive Bacteriamentioning
confidence: 99%
See 2 more Smart Citations